Payout policies of privately held firms: Flexibility and the role of income taxes - Martin Jacob; Annette Alstadsæter (Arbeitskreis Quantitative Steuerlehre (arqus), 2013)
We study the importance of owner wages and dividends as alternative payout channels in privately held firms. Using data on all Swedish closely held corporations and their owner-managers over the period 2000 - 2009, we find that dividends comprise one-fourth of total payout to owner-managers. Dividends are used as a flexible payout channel. Wages are the preferred payout channel and are rather sticky. Choice of payout channel and level of payout are affected by dividend and wage taxation. Consistent with the difference in flexibility across payout channels, shareholder taxes have a stronger impact on dividends than on wages.
Keywords: G30; G35; H24; H25; 330; Payout Policy; Private Firms; Owner-managers; Dividends; Owner wages; Income Taxes